Annual appearance of hydrogen chloride on Mars and a striking similarity with the water vapor vertical distribution observed by TGO/NOMAD - Aoki, S; Daerden, F; Viscardy, S; Thomas, IR; Erwin, JT; Robert, S; Trompet, L; Neary, L; Villanueva, GL; Liuzzi, G; Crismani, MMJ; Clancy, RT; et al. (Wiley, 2021)
Hydrogen chloride (HCl) was recently discovered in the atmosphere of Mars by two spectrometers onboard the ExoMars Trace Gas Orbiter. The reported detection made in Martian Year 34 was transient, present several months after the global dust storm during the southern summer season. Here, we present the full data set of vertically resolved HCl detections obtained by the NOMAD instrument, which covers also Martian year 35. We show that the particular increase of HCl abundances in the southern summer season is annually repeated, and that the formation of HCl is independent from a global dust storm event. We also find that the vertical distribution of HCl is strikingly similar to that of water vapor, which suggests that the uptake by water ice clouds plays an important role. The observed rapid decrease of HCl abundances at the end of the southern summer would require a strong sink independent of photochemical loss.